Have amenities become relatively more important than firm productivity advantages in metropolitan areas? - Richard Deitz; Jaison R. Abel (Federal Reserve Bank of New York, 2008)
We analyze patterns of compensating differentials to determine whether a region's bundle of site characteristics has a greater net effect on household location decisions relative to firm location decisions in U.S. metropolitan areas over time. We estimate skill-adjusted wages and attribute-adjusted rents using hedonic regressions for 238 metropolitan areas in 1990 and 2000. Within the framework of the standard Roback model, we classify each metropolitan area based on whether amenities or firm productivity advantages dominate and analyze the extent to which these classifications change between 1990 and 2000. We then decompose compensating differentials into amenity and firm productivity advantage components and examine how these components change. Empirical results suggest that while the relative importance of amenities appears to have increased slightly between 1990 and 2000, firm productivity advantages continued to dominate amenities in the vast majority of metropolitan areas during this decade.
Keywords: R23; R30; 330; Compensating differentials; quality of life; productivity